2011
DOI: 10.1080/14662043.2011.615171
|View full text |Cite
|
Sign up to set email alerts
|

Public Accounts Committees in the Commonwealth: oversight, effectiveness, and governance

Abstract: The World Bank, Consultant on Legislative AffairsFor the past 15 years the international community has assumed that by strengthening legislative capacity, legislatures are better equipped to oversee government activity and spending, to keep governments accountable, to secure good governance, prevent corruption, and create the conditions for sustainable economic development. The purpose of the present paper is to test this set of assumptions by focusing on one of the oversight tools that the international commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Finally, while some of previous analyses (e.g. by Pelizzo, 2011) showed that the presence of opposition MPs on the PAC is a major determinant of the number of meetings held and of the number of reports produced by the committee, other studies (e.g. by Pelizzo, 2013) did not detect such a relationship-which is why Stapenhurst, Pelizzo and Jacobs (2013) suggested that the determinants of PAC effectiveness are very much country and region-specific.…”
Section: The Organization Of Pacsmentioning
confidence: 63%
See 2 more Smart Citations
“…Finally, while some of previous analyses (e.g. by Pelizzo, 2011) showed that the presence of opposition MPs on the PAC is a major determinant of the number of meetings held and of the number of reports produced by the committee, other studies (e.g. by Pelizzo, 2013) did not detect such a relationship-which is why Stapenhurst, Pelizzo and Jacobs (2013) suggested that the determinants of PAC effectiveness are very much country and region-specific.…”
Section: The Organization Of Pacsmentioning
confidence: 63%
“…Hence, the size of the support staff is the fourth factor that we consider in our analysis. Note however that the importance of having a large and well trained staff, has been documented for the Commonwealth as a whole (Pelizzo, 2011), Asia (Stapenhurst, Pelizzo, Jacobs, 2013) and the Pacific (Pelizzo, 2013) but not elsewhere or at least not significantly so. 6 Hence, it is worth investigating whether the performance of East African…”
Section: The Organization Of Pacsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies assumed that it was appropriate to do so, other studies decided to inquire as to whether the levels of output (meetings, hearings) were actually related to frequency with which PACs were able to achieve policy relevant results (Pelizzo, 2011), while other studies (Bianchi, 2012) equated the success of PACs with their ability to save public money.…”
Section: From Activity To Performancementioning
confidence: 99%
“…Specifically, McGee (2002) suggested that the size of a PAC, the partisan affiliation of the PAC Chairperson and the size of the staff at the disposal of a PAC are largely responsible for its success. Building on the work by McGee (2002), Pelizzo (2011) suggested that the partisan composition of the PAC membership, that is whether opposition forces are adequately represented in the committee, is very important.…”
mentioning
confidence: 99%